Analysis of Chinese Culture in the Film I Am What I Am (2021) by Sun Haipeng Using Semiotic Roland Barthes - Rositawati, Pingkan; Siregar, Sheyra Silvia; Pamuji, Dian Yuni (Universitas Negeri Semarang, 2025)
This article discusses the analysis of Chinese culture in the film I Am What I Am (2021) directed by Sun Haipeng, using semiotic Roland Barthes. The aim of this research is to uncover the cultural meanings conveyed through visual and narrative symbols in the film. This study employs a descriptive qualitative method, in which data is collected through observation of scenes that contain elements of Chinese culture such as the lion dance, salted fish, lanterns, and others. The analysis is carried out through three levels of meaning according to Barthes: denotation (literal meaning), connotation (cultural meaning), and myth (ideological meaning).